ONE HUNDRED YEARS OF EURASIANISM NARRATIVES: SOME NOTES ON METHODOLOGY (Journal of Philosophy Culture and Political Science, 2021)
Eurasianism has approached its centennial milestone with a plethora of theoretical and practical discourses. Transforming from the level of philosophical, political and civilizational theory, it gradually disintegrated into a multitude of disjunct critical studies, geopolitical projects and regional economic strategies. Moreover, geographically, Eurasianism has become very diverse: its beneficiaries are many countries and in some anti-globalist versions – the entire “non-Western” world. Accordingly, the geography of the schools of Eurasian studies has expanded to the maximum: having emerged among Russian emigrants in Europe, today the Eurasian scientific communities are already present on all continents. The academization of discourse does not add clarity to the narratives, in some ways blurring, and in some ways extremely narrowing them down. The authors present their analysis of the current situation in the format of philosophical and methodological notes and state that the concept of “Eurasia” that had emerged almost a century ago in a specific historical context, in the 21st century has become so dynamic and multifaceted that it is capable of performing only the nominal role of an umbrella term; the key characteristic of contemporary concepts of Eurasia are their polyphony and the open nature of terminology in the field. The authors apply a number of explanatory concepts such as “lacuna”, “time and space”, “instrumentalist approach”, “ideology”, “pragmatism”, etc., to discuss the paradox of the Eurasian discourse: while it is conceived to be an integrating concept – both on the theoretical, and on practical levels – it is also a separating term. The article examines the dynamic communities of Eurasian narratives. It is emphasized that their incomplete nature is a consequence of the phenomenon evolution and of modern historical realities. The authors come to conclusion that in the local circumstances, the discrete concepts of Eurasianism are able to solve the problems that are beyond the power of “classical” paradigmatic research methods and that the synthesis approach to the phenomenon of Eurasianism opens up new prospects for its comprehension and use. The article is written with the support of “Art Eurasia” Public Foundation.Key words: Eurasianism, Eurasian studies, narrative, polyphony, lacuna.